2002
DOI: 10.1080/07399330290112416
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Physical Activity in Preparing Women for Pregnancy and Delivery in Poland

Abstract: Our aim in conducting this study is to document different forms of recreational activities chosen by women before and during pregnancy and to answer the question of how women prepared themselves physically to deliver their babies. We included 266 women who were in the third trimester of their pregnancies in this study. (The women were randomized.) Methods of recreation were divided into two groups: active (involving physical exercise) and passive (physical exercise not involved). From our findings we suggest t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 1 publication
3
20
1
1
Order By: Relevance
“…These results were not expected and indicated that the women in this study may have considered their discomfort inherent in their condition. The results, however, are in line with those of other studies (Duncombe et al, 2009;Evenson et al, 2009;Haakstad et al, 2009;Rutkowska & Łepecka-Klusek, 2002). Interpersonal barriers to leisure PA, such as lack of support, were infrequently cited by our survey participants.…”
Section: Barriers To Physical Activity According To the Socioecologisupporting
confidence: 81%
“…These results were not expected and indicated that the women in this study may have considered their discomfort inherent in their condition. The results, however, are in line with those of other studies (Duncombe et al, 2009;Evenson et al, 2009;Haakstad et al, 2009;Rutkowska & Łepecka-Klusek, 2002). Interpersonal barriers to leisure PA, such as lack of support, were infrequently cited by our survey participants.…”
Section: Barriers To Physical Activity According To the Socioecologisupporting
confidence: 81%
“…12 To date, however, few studies have addressed the reasons why women reduce their physical activity during pregnancy. 13,14 In addition to the limited quantitative studies, we are aware of only three qualitative studies exploring the issues regarding physical activity during pregnancy, 5, 15, 16 and two were conducted in Detroit, Michigan among Hispanic women. 5, 16 We sought to expand the information currently available by conducting analyses of two studies in central North Carolina.…”
Section: Introductionmentioning
confidence: 99%
“…A consensus panel on physical activity in the prevention and treatment of obesity concluded that the development of physical activity interventions for pregnant women represented a potentially fruitful avenue for the prevention of overweight and obesity (Grundy, et al, 1999). However, to date few studies have addressed the reasons why women reduce their physical activity during pregnancy and how it changes into the postpartum period (Clarke & Gross, 2004; Rutkowska & Lepecka-Klusek, 2002). Exploration into the correlates of physical activity during pregnancy is one of the first steps to understanding where to focus interventions, building upon existing qualitative work (Devine, Bove, & Olson, 2000; Evenson, Moos, Carrier, & Siega-Riz, 2008; Kieffer, Willis, Arellano, & Guzman, 2002).…”
Section: Introductionmentioning
confidence: 99%